Analysis of Factors Affecting Company Performance (Case Study of a Honda Motorcycle Company in Medan City) - Sri Lestari, Saragih; Maksum , Azhar; Gaddafi, Muammar (Jurnal Multidisiplin Indonesia, 2023)
In this era of globalization, every business activity develops for the better which results in increasingly fierce competition in the business world for the company itself. A good company at least has good performance and can also provide solutions to problems that may be encountered in the future. Managers must be able to translate the vision and mission into concrete steps so that they can be implemented. In business, it is very important for this company to continue to maintain maximum company performance. The importance of company performance because company performance can be seen from the company's ability to achieve its goals by utilizing resources efficiently and effectively. By measuring the performance of the company, then of course you can find out how far the level of achievement of the company's goals goes. To improve company performance it is very important to know how internal control is running, who is involved in the budgeting process and whether there is transparency to improve company performance and achieve its vision and mission. The population in this study were all employees who worked at 41 Honda motorcycle companies in Medan City. Sampling using purposive sampling method and the test tool used is multiple linear regression analysis. The results of this study prove that internal control, the budgeting process has a positive and significant effect on company performance. Transparency negative and significant effect on company performance. Organizational characteristics are able to moderate the effect of internal control on company performance. Organizational characteristics are unable to moderate the effect of the budgeting process and transparency on company performance.